MECHANISMS FOR COORDINATION OF MASTER PLANNING AND LOT SIZING WITHIN A HIERARCHICAL PRODUCTION PLANNING MODEL - Leisten, Rainer; Reusch, Pascal (International Journal of Computing, 2014)
This paper presents a simulation based analysis of different coordination mechanisms in Hierarchical Production Planning. According to the results of the simulations the effects of Aggregation and Capacity Assignments on the overall costs are discussed.